Spray dried apple powder: Qualitative, rheological, structural characterization and its sorption isotherm. (1st August 2022) - Qadri, Tahiya; Naik, Haroon Rashid; Hussain, Syed Zameer; Naseer, Bazila; Bhat, Tashooq; Vijaykumar; Wani, Faheem J
Abstract: Qualitative analysis of the spray dried apple powder (SDAP) was carried out which revealed slightly higher moisture content (2.91%) and water activity (0.217) as compared to the apple powder available in market (MP). Solubility, dispersibility and sinkability of SDAP was comparable to MP while significantly (p < 0.05) high wettability values were recorded for SDAP indicating its improved reconstitutional properties. Low cohesiveness, Carr's index while as high angle of repose was recorded for SDAP as compared to MP depicting its excellent flow characteristics. DSC thermograms showed high Tg, Ts, ΔH and low ΔCp of SDAP revealing better stability and amorphous nature of SDAP. XRD diffractograms also depicted presence of single broad peak in SDAP further validating its amorphous structure. Particle size distribution showed that SDAP comprised of 62% large sized particles with overall average particle mean diameter (D4, 3 ) of 342.9 nm. Rheological studies showed that SDAP exhibited non-Newtonian behaviour. Storage modulus (G′) was found higher than loss modulus (G″) in SDAP as compared to MP. Sorption isotherm revealed that SDAP was stable when stored at relative humidity of less than 25%. Oswin and GAB models predicted the sorption behaviour of SDAP effectively as depicted by high R 2 values. Highlights: Spray dried apple powder (SDAP) recorded better flow characteristics and similar reconstitutional behaviour. Reduced particle size of SDAP yielded its enhanced handling characteristics. Synergistic incorporation of maltodextrin and Gum arabic resulted in enhanced Tg of SDAP. Rheological study showed that SDAP when reconstituted held structure better. Stability diagram revealed that Tg decreases as a function of aw .